PP.14 Progesterone Modulates Cervical Antimicrobial Immunity. (26th April 2013) - James, CP; Klein, N; Bajaj-Elliott, M; Peebles, D
Abstract : Introduction: Human beta defensins (HBD1, 2.3) have antimicrobial and immunomodulatory properties and are components of the cervical mucus plug. Vaginal progesterone delays delivery in women with cervical shortening, but the mechanism(s) underlying this effect remain undetermined. This study describes the expression of HBDs by cervical epithelia in response to stimulation with classical infective and inflammatory agonists and progesterone. Methods: The human endo-cervical cell-line End1/E6E7 and ecto-cervical cell-line Ect1/E6E7 were stimulated with bacterial (Lipopolysaccharide, LPS; Peptidoglycan, PGN) and inflammatory (Interleukin 1 beta, IL-1β; Interferon gamma, IFNγ) agonists and progesterone for up to 24 hours. HBD secretion was assessed by ELISA. Results: End1/E6E7 HBD1 expression did not respond to stimulation. HBD1 secretion by Ect1/E6E7 cells more than doubled in response to IL-1β (p = 0.0002) and IFNγ (p = 0.02), and was suppressed by progesterone (p = 0.02). End1/E6E7 HBD2 release almost doubled in response to LPS (p = 0.02) and progesterone (p = 0.01). HBD2 expression by Ect1/E6E7 cells doubled in response to LPS (p = 0.005) and halved after stimulation with progesterone (p = 0.006). End1/E6E7 HBD3 expression increased in response to LPS (p = 0.0009), and almost doubled after stimulation with PGN (p = 0.0003) and IFNγ (p = 0.027). End1/E6E7 HBD3 secretion almost tripled in response to incubation with progesterone (p = 0.003). Conclusion: Bacterial products elicited differential expression of HBDs in End1/E6E7 and Ect1/E6E7 cells. Progesterone mediated an increase in HBD2 and HBD3 secretion by endo-cervical cells but suppressed HBD1 and HBD2 secretion by ecto-cervical cells; this effect may augment cervical host defence, representing a novel mechanism by which progesterone may contribute to delaying the onset of preterm labour.